The Influence of Entrepreneurial Characteristics on the Performance of Tourism Vlogger Entrepreneurs - Xie, Qing; Liu, Lisha; Malik, Haider; Chupradit, Supat; Chupradit, Priyanut Wutti (Frontiers in Psychology, 2021)
The current Internet revolution has changed the entrepreneurial opportunities and trends. This study explores the relationship between entrepreneurial characteristics (e.g., innovation, leadership, planning, and sociability) and the performance of entrepreneurial vloggers in India. In addition, this study considers the mediating effect of entrepreneurial intentions. This study is cross-sectional, and it considered 128 entrepreneurial vloggers for the analysis. The SmartPLS application was used to estimate the structural equation modeling (SEM) analysis for the estimation of reliability and validity along with the path relationship. The findings are more important as the entrepreneurial characteristics can meaningfully predict the performance of entrepreneurial vloggers in a positive direction. Moreover, the relationship between entrepreneurial characteristics and the performance of entrepreneurs is partially mediated by entrepreneurial intentions. These findings have important implications for vloggers in Indian or other countries with similar nature. This study has also put some future research directions at the end.